Enhancing potato productivity in Bangladesh: gamma irradiation-induced resistance to bacterial wilt caused by Ralstonia solanacearum - Haque, M M; Miah, M S; Hasna, M K; Afroge, M; Akter, S; Babu, M R (Bangladesh Journal of Nuclear Agriculture, 2025)
Bacterial wilt caused by Ralstonia solanacearum is one of the most devastating diseases affecting potato cultivation in Bangladesh, resulting in substantial yield losses and posing a major barrier to sustainable production and export competitiveness. This study aimed to investigate the potential of gamma irradiation to induce resistance against bacterial wilt in potato cultivars and improve overall productivity. Field experiments were conducted across three major potato-growing regions—Mymensingh, Rangpur, and Cumilla—using eight widely cultivated potato varieties: Asterix, Granola, Musica, Cumbia, Cardinal, Diamond, Santana, and Sunshine. Dry tubers were irradiated with gamma rays at doses of 20, 30, and 40 Gy, and the resulting M1V1 generation was cultivated for performance evaluation. Molecular identification of R. solanacearum from tuber and soil samples using species-specific primers (PS-1/PS-2) confirmed a consistent 553 bp amplicon, validating pathogen presence. Results indicated that gamma irradiation induced variable morphological and pathological responses across cultivars. At 20 Gy, Asterix and Cardinal demonstrated notable increases in tuber number and weight, suggesting a stimulatory effect on growth and yield. In contrast, higher doses (30 Gy and 40 Gy) were more effective in reducing the incidence of bacterial wilt, likely through mutation-induced resistance mechanisms. These findings underscore gamma irradiation's dual role in enhancing both disease resistance and yield potential. The study provides valuable insights into mutation breeding as a strategic tool for managing soil-borne bacterial diseases and improving the productivity and resilience of potato crops under changing climatic and phytosanitary conditions in Bangladesh. Bangladesh J. Nuclear Agric., 39(1): 101-113, 2025